edukasi lalu lintas EDUKASI RAMBU LALU LINTAS MENGGUNAKAN MEDIA ULAR TANGGA DI SD NEGERI SIWALANPANJI - Eni Nurhayati; Galuh Kartika Dewi; Ery Rahmawati; Nurul Rahmawati; Dewi Qolbi Ma'rifatus Sholikhah; Lailatul Masruroh; Putri Suwarni; Rani Anggreni; Reka Angraeni; Silviatul Azmi; Lisnawati Matruty (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
Abstract – every year traffic accidents are increasing. The main factor causing an increase in traffic accidents is drivers who do not understand traffic signs and deliberately violate these rules. Therefore, to make it easier to understand traffic signs, socialization activities can be carried out from an early age so that they are able to develop a positive spirit when they are adults. One way that can help foster student activity and comfort in the teaching and learning process takes place is to deliver material for students aged 9-11 years by using traffic learning media in the form of an animation so that students will more easily understand what they are learning. This learning media is interactive so that it makes students more active and independent because there are also varios kinds of interesting media signs. In this case students continue to be enthusiastic and have a willingness to participate inlearning. In this research uses qualitative methods. The implementation of this community service program is carried out through four stages, namely 1) the preparation stage 2) the planning stage 3) the implementation stage 4) the program sustainability evaluation stage. And the activities carried out by the siwalanpanji public elementary school children are very useful, this is because the children understand the meaning of orders through signs and restrictions on the roads. Children’s understanding needs to be honed so that children know that everything that is outside has instructions and prohibitions. Keyword: Learning Media, Animation and snakes and ladders, Traffic Signs